Analysis of 5-Azacytidine Resistance Models Reveals a Set of Targetable Pathways - Minařík, Lubomír; Pimková, Kristýna; Kokavec, Juraj; Schaffartziková, Adéla; Vellieux, Fréderic; Kulvait, Vojtěch; Daumová, Lenka; Dusilková, Nina; Jonášová, Anna; Vargová, Karina Savvulidi; Králová Viziová, Petra; Sedláček, Radislav; et al. (Cells, 2022)
The mechanisms by which myelodysplastic syndrome (MDS) cells resist the effects of hypomethylating agents (HMA) are currently the subject of intensive research. A better understanding of mechanisms by which the MDS cell becomes to tolerate HMA and progresses to acute myeloid leukemia (AML) requires the development of new cellular models. From MDS/AML cell lines we developed a model of 5-azacytidine (AZA) resistance whose stability was validated by a transplantation approach into immunocompromised mice. When investigating mRNA expression and DNA variants of the AZA resistant phenotype we observed deregulation of several cancer-related pathways including the phosphatidylinosito-3 kinase signaling. We have further shown that these pathways can be modulated by specific inhibitors that, while blocking the proliferation of AZA resistant cells, are unable to increase their sensitivity to AZA. Our data reveal a set of molecular mechanisms that can be targeted to expand therapeutic options during progression on AZA therapy.
Keywords: signální transdukce; Phosphatidylinositol 3-Kinases; anotace sekvence; azacytidin; protoonkogenní proteiny c-akt; Drug Resistance, Neoplasm; Proto-Oncogene Proteins c-akt; Molecular Sequence Annotation; chemorezistence; zvířata; Animals; Mice, SCID; Transcriptome; myši; Azacitidine; fosfatidylinositol-3-kinasy; Mice; transkriptom; biologické modely; Models, Biological; myši SCID; DNA, Neoplasm; Reproducibility of Results; DNA nádorová; Signal Transduction; reprodukovatelnost výsledků